Reliability analysis of pre-competitive stress instrument of young Brazilians soccer players - Barroso Hirota, V.; Lopes Verardi, C. E.; De Marco, A. (European Journal of Physical Education and Sport Science, 2016)
The aim of this research is to test the stress instrument, and identify the symptoms of pre-competitive stress of young Brazilians athletes from soccer, and throw a descriptive research we evaluated 300 male Brazilian soccer players aged between 10-17 years (age average 13.45±2.37) using a Likert scale named List of Symptoms of "Stress" Pre-Competitive; as statistical it was made the descriptive statistical, reliability analysis counting with the Alpha´s Coefficient and Factorial exploratory analysis of the instrument. The results showed an excellent reliability of the issues of the instrument, and detected six factors, demonstrating that the youth athletes has a moderate level of stress and concluded that another analysis need to be done in future studies.